Digital transformation and enterprise violation risk: A ‘motivation-opportunity-attitude’ framework - Xinlan Wang; Nan Wang; Weizhang Sun; Andi Xu; Zhiguo Zhang (Heliyon)
In the evolving digital economy, digital transformation has emerged as an important strategic choice for enterprises. Their comprehensive and innovative characteristics have instigated a paradigm shift in enterprise governance ideologies and models. However, this transformation has also introduced heightened demands and challenges to enterprise governance mechanisms during the transitional phase. This study examined the influence of digital transformation on enterprise violation risk using data from Chinese A-share listed companies from 2017 to 2021. The analysis revealed an inverted U-shaped relationship between the degree of digital transformation and enterprise violation risk. This relationship was underpinned by three fundamental dimensions: motivation, opportunity, and management attitude. These dimensions were elucidated through mechanisms involving risk perception, management agency costs, and management responsibilities. These conclusions were reached even after rigorous tests for endogeneity and stability. Furthermore, this study probed specific scenarios in which digital transformation influences enterprise violation risk. This finding revealed that internal control mechanisms and external analysts’ attention moderate this relationship. As the effectiveness of internal controls and the attention of external analysts increase, the inflection point of the inverted U-shaped curve shifts to the left, and the curve progressively smoothens. Thus, greater internal control effectiveness and the governance impact of external analysts can positively affect the correlation between digital transformation and enterprise violation risk, thereby facilitating digital resources to empower enterprise governance. This study contributes to the theoretical discourse on the implications of digital transformation for enterprise governance, particularly in the context of evolving market dynamics. It offers valuable insights and recommendations for effectively driving digital transformation processes.